Strategi Kesantunan Tuturan Imperatif Dalam Manga Meitantei Konan Vs Kaitou Kiddo Karya Aoyama Goushou (2010) - Sri Wahyuni, Ni Nengah; Yuliani Giri, Ni Luh Kade; Andry Anita Dewi, Ni Made (Humanis, 2016)
This research entitled "Politeness Strategy Imperative Speech in Meitantei Konan vs Kaitou Kiddo Comic by Aoyama Goushou." Politeness Strategies and Politeness Scale theory proposed by Brown and Levinson were applied to analyze the data. The aim of the research was to identify the use of politeness strategy and causative factors of politeness strategy use in the data source. As a result, three use of politeness strategies were identified; there were bald on record politeness strategy, positive politeness strategy, and negative politeness strategy. The use of politeness strategies were influenced by three factors: power, social scale, and degree of imposition.